2011
DOI: 10.1007/s11325-011-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 10 days of modest intermittent hypoxia on circulating measures of inflammation in healthy humans

Abstract: These findings suggest that (1) a more substantial or a different pattern of hypoxemia might be necessary to activate systemic inflammation, (2) the system may need to be primed before hypoxic exposure, or (3) increases in inflammatory markers in patients with OSA may be more related to other factors such as obesity or nocturnal arousal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…We verified O 2 transitions in media using direct real-time measurements; however, the ultimate question is whether such changes in O 2 availability induce any biological responses in cells and if so, what O 2 level and duration of hypoxia is required. Similar to others, we documented both HIF and NF-κB activation after IH exposure (Nanduri et al 2008;Oliver et al 2009;Prabhakar et al 2010;Yuan et al 2011;Quintero et al 2013;Wang et al 2013a), confirming thus possible molecular mechanisms for IH-related pro-inflammatory effects (Querido et al 2012;Baessler et al 2013;Murase et al 2013;He et al 2014). Furthermore, the severity of exposure required for NF-κB activation was of similar intensity to that required for HIF activation (cycling between 4% and 1% O 2 ), potentially suggesting shared intracellular pathways and mutual interactions between these two transcription factors, as suggested previously (Jung et al 2003;Scholz et al 2013).…”
supporting
confidence: 90%
“…We verified O 2 transitions in media using direct real-time measurements; however, the ultimate question is whether such changes in O 2 availability induce any biological responses in cells and if so, what O 2 level and duration of hypoxia is required. Similar to others, we documented both HIF and NF-κB activation after IH exposure (Nanduri et al 2008;Oliver et al 2009;Prabhakar et al 2010;Yuan et al 2011;Quintero et al 2013;Wang et al 2013a), confirming thus possible molecular mechanisms for IH-related pro-inflammatory effects (Querido et al 2012;Baessler et al 2013;Murase et al 2013;He et al 2014). Furthermore, the severity of exposure required for NF-κB activation was of similar intensity to that required for HIF activation (cycling between 4% and 1% O 2 ), potentially suggesting shared intracellular pathways and mutual interactions between these two transcription factors, as suggested previously (Jung et al 2003;Scholz et al 2013).…”
supporting
confidence: 90%
“…transcription factor nuclear factor-kappa β). In contrast to the results of intermittent hypoxia in mice and rats, nocturnal exposure to intermittent hypoxia in healthy humans for 10 and 14 days did not increase markers of systemic inflammation 40,41 .…”
Section: Animal and Human Intermittent Hypoxia Experimentscontrasting
confidence: 95%
“…Querido et al (29) reported that intermittent hypoxia as a result of airway obstruction would not be responsible for systemic inflammation, which may support that increased systemic inflammation in OSA patients may be more closely associated with other factors. In our study, we found old age, male gender, current smoking status and high AHI level as risk factors of periodontitis.…”
Section: Discussionmentioning
confidence: 94%